2017
DOI: 10.1093/heapol/czx100
|View full text |Cite
|
Sign up to set email alerts
|

A new use for an old tool: maternity waiting homes to improve equity in rural childbirth care. Results from a cross-sectional hospital and community survey in Tanzania

Abstract: Limited quality of childbirth care in sub-Saharan Africa primarily affects the poor. Greater quality is available in facilities providing advanced management of childbirth complications. We aimed to determine whether Maternity Waiting Homes (MWHs) may be a tool to improve access of lower socio-economic women to such facilities. Secondary analysis of a cross-sectional hospital survey from Iringa District, Tanzania was carried out. Women who delivered between October 2011 and May 2012 in the only District facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 29 publications
6
49
3
Order By: Relevance
“…This study showed that women in the lower wealth quintiles (1st and 2nd ) were more likely to use MWH services than those women in the highest (5th ) quantile. Similar ndings have also been reported by studies conducted in Gurage zone, Central Ethiopia, Tanzania, Zambia and Malawi, all of which highlighted that poorer women were more likely to use MWH services than women in the wealthiest quintile [14,[39][40][41][42]. The possible reason might be that staying in MWHs may be the only means the poorer women could access obstetric care and overcome delay in reaching the HIs as a result of exorbitant transportation cost and poor road condition.…”
Section: Discussionsupporting
confidence: 84%
“…This study showed that women in the lower wealth quintiles (1st and 2nd ) were more likely to use MWH services than those women in the highest (5th ) quantile. Similar ndings have also been reported by studies conducted in Gurage zone, Central Ethiopia, Tanzania, Zambia and Malawi, all of which highlighted that poorer women were more likely to use MWH services than women in the wealthiest quintile [14,[39][40][41][42]. The possible reason might be that staying in MWHs may be the only means the poorer women could access obstetric care and overcome delay in reaching the HIs as a result of exorbitant transportation cost and poor road condition.…”
Section: Discussionsupporting
confidence: 84%
“…Data from the National Bureau of Statistics (NBS) show that only 29% of all women and 34% of married women in Tanzania use any contraceptive methods [1]. Tanzania is among ten countries with the highest number of maternal and neonatal deaths [2]. The current maternal mortality ratio is 556 deaths per 100,000 live births and neonatal mortality rate is estimated at 25 per 1000 live births [3].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing a new intervention like MWHs to a health system, however, incurs additional costs to providers and/or users . The pricing policies of MWHs and delivery care vary within and across countries ranging from free of charge as in Ethiopia and Nepal, to paying some amount of money like in Guatemala, Tanzania, and Sierra Leone, varying from a flat rate to payment per day . Considering the amount of payment for maternity services is important in order to assess the affordability and utilization of MWHs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The pricing policies of MWHs and delivery care vary within and across countries ranging from free of charge as in Ethiopia and Nepal, to paying some amount of money like in Guatemala, Tanzania, and Sierra Leone, varying from a flat rate to payment per day. [7][8][9][10][11][12] Considering the amount of payment for maternity services is important in order to assess the affordability and utilization of MWHs. The previous studies from Zambia found that women's willingness to pay for MWH utilization depended on the quality of services.…”
Section: Introductionmentioning
confidence: 99%